The Production of Biodiesel and Bio-kerosene from Coconut Oil Using Microwave Assisted Reaction - Saifuddin N.; Siti Fazlili A.; Kumaran P.; Pei-Jua N.; Priathashini P. (Institute of Physics Publishing, 2023)
Alternative fuels; Biodiesel; Biofuels; Catalysts; Distillation; Fatty acids; Microwave generation; Microwaves; Saturated fatty acids; Transesterification; Vegetable oils; Catalyst concentration; Coconut oil; Lauric acid; Low emission; Microwave power; Microwave-assisted reactions; Myristic acid; Transesterification process; Kerosene; biofuel; catalyst; distillation; energy resource; fatty acid; hydroxide; microwave radiation; power generation; renewable resource; research work; sodium; vegetable oil